Tumour-to-Tumour Metastasis Phenomenon: Metastatic Prostatic Adenocarcinoma within an Anaplastic Oligodendroglioma in the Brain of a Dog. (November 2018) - Ros, C.; Fernández-Flores, F.; de la Fuente, C.; Pi, D.; Añor, S.; Planellas, M.; Pumarola, M.
Summary: A 10-year-old entire male French bulldog was presented following clusters of generalized tonic–clonic epileptic seizures. Neurolocalization was consistent with a lesion in the left forebrain. Magnetic resonance imaging of the brain revealed a large, ill-defined, intra-axial, space-occupying lesion at the level of the left temporal and parietal lobes, causing marked compression of the adjacent parenchyma. Computed tomography of the thorax and abdomen was consistent with disseminated metastatic disease. The dog was humanely destroyed and subjected to necropsy examination. Histological examination of the brain revealed a metastasis of prostatic carcinoma within an anaplastic oligodendroglioma in the left forebrain. To the author's knowledge, this is the first report describing clinical, imaging and histopathological features of an intracranial tumour-to-tumour metastasis in the brain of a dog. Graphical abstract: Tumour-to-tumour metastasis phenomenon in the brain of a dog, where a prostatic adenocarcinoma metastatizes within an anaplastic oligodendroglioma. An intratumoural mass resembling metastatic foci is present in the center of the oligodendroglial tumour. PanCK immunopositivity in the brain is observed, indicating their epithelial origin demonstrating this phenomenon.